KADINLAR BASKETBOL LİGİNDE OYNAYAN SPORCULARIN BEDENİ BEĞENME VE ALGILANAN ESENLİK DURUMLARININ İNCELENMESİ - SÖYLER, DİDEM YAVUZ (Fırat Üniveristesi, 2021)
Bedeni beğenme kişinin vücudunun çeşitli bölümleri hakkında bütüncül bir değerlendirme yaparak herhangi yargıya varmasıdır. Günümüzde kadın bedenine atfedilen beklentiler çeşitli değişkenliklerle değişmektedir. Bu bağlamda insanın daha kaliteli ve sağlıklı bir yaşama kavuşması için hayatın tamamına bir bütün olarak bakabilme sanatı wellness (esenlik) olarak tanımlanır. Bedeni beğenme, bedene karşı olumlu duygulara sahip olunması ve bedenin olduğu gibi kabul görmesi anlamına gelmektedir. Kadınlar basketbol liginde oynayan sporcuların bedeni beğenme ve algılanan esenlik durumları değişmektedir genel hipotezinden yola çıkılarak geliştirilen çalışma; 2019-2020 Kadınlar Basketbol Süper Liginde yer alan 14 takım ve bu takımlar da oynayan 162 kadın basketbolcuların bedeni beğenme ve algılanan düzeylerini tespit etmek, demografik değişkenlerin bu düzeyler üzerinde etkili olup olmadığını belirlemek ve bu iki kavram arasındaki ilişkiyi incelemektir Araştırmaya katılan sporcuların; eğitim değişkenine göre yüksek lisans eğitim düzeyine sahip sporcuların (x2: 9,083; p<0,05), 6-10 ve 11 ve üstü spor yılına sahi, fiziksel görünümleri incelendiğinde kendini normal olarak gören (x2: 7,475; p<0,05), güzellik algılarına göre kendini çok güzel gören sporcuların (x2: 5,137; p<0,05), duygu durumuna göre kendini kötü hisseden sporcuların (x2: 17,126; p<0,05) beden beğenilerinin ve algılanan esenlik düzeylerinin yüksek olduğu ve anlamlı bir farklılık oluşturduğu görülmüştür. Katılımcıların algılanan esenlik ve bedeni beğenme algılarını pozitif yönde etkilediği görülmüştür (r:0,526; p<0.001).

INVESTIGATION OF THE LIKE AND PERCEIVED WELL-BEING STATES OF ATHLETES PLAYING IN THE WOMEN'S BASKETBALL LEAGUE Body liking is a person's making a holistic assessment of various parts of his body and making any judgments. Today, the expectations attributed to the female body are changing with various variability. In this context, the art of looking at the whole of life as a whole in order for a person to have a better quality and healthy life is defined as wellness. Liking the body means having positive feelings towards the body and being accepted as it is. A high level of body liking also shows parallelism with perceived well-being. The study developed on the basis of the general hypothesis that the body liking and perceived well-being of the athletes playing in the women's basketball league changes; The aim of this study is to determine the body liking and perceived levels of 14 teams in the 2019-2020 Women's Basketball Super League and 162 female basketball players playing in these teams, to determine whether demographic variables are effective on these levels and to examine the relationship between these two concepts. The athletes participating in the research; According to the education variable, the athletes with a graduate education level (x2: 9,083; p<0.05), who have 6-10 and 11 and above sports years, who see themselves as normal when their physical appearance is examined (x2: 7.475; p<0.05) It was found that the athletes who see themselves very beautiful according to their beauty perceptions (x2: 5,137; p<0.05), and the athletes who feel bad according to their emotional state (x2: 17,126; p<0.05) have high body liking and perceived well-being levels. difference was observed. It was observed that the participants' perceptions of perceived well-being and body liking had a positive effect (r:0.526; p<0.001).
Investigation of the like and perceived well-being states of athletes playing in the women's basketball league
Keywords: Spor